NURSING CONSULTATION TEACHING IN NURSES’ TRAINING: A BIBLIOMETRIC STUDY - Jesus, Ludmila Anjos de; Costa, Laura Emmanuela Lima; Oliveira, Monalliza Gama; Souza, Virgínia Ramos dos Santos; Silva, Gilberto Tadeu Reis da; Cordeiro, Ana Lúcia Arcanjo Oliveira; Silva, Rudval Souza da (Cogitare Enfermagem, 2022)
Objective: to identify the Brazilian scientific production about Nursing consultation teaching in nurses’ training. Method: a descriptive study of a bibliometric nature conducted in the portal of Biblioteca Virtual em Saúde and in PubMed from April to May 2021, with the following inclusion criteria: full articles, in Portuguese or English, published from 2009 to 2020. Results: a total of 13 studies were identified, of which four were published in a B2 journal from the Northeast region, although with predominance of papers from the South region (38.46%), with the experience report type standing out. The most frequently observed themes were related to the teaching methodologies, especially the active ones with use of technological tools. “Nursing consultation” was not found to be one of the most frequent keywords. Conclusion: by verifying the incipience of the production on the theme, this study provides subsidies for expanding this knowledge area, reverberating in improvements in Nursing consultation teaching and in nurses’ training.